HISTOPATHOLOGY LIVER AND KIDNEY OF Pangasius hypophthalmus THAT WERE IMMERSED IN Lawsonia inermis L. SOLUTION - Margaret Viviani; Morina Riauwaty; Iesje Lukistyowati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT             This research has been conducted on June until December 2017 in Laboratory of Parasites and Fish Diseases of Fisheries and Marine Faculty, University of Riau. The aimed of this research was to know the structure of liver and kidney tissues of Pangasius hypophthalmus that were immersed in Lawsonia inermis L. solution for preventing the of Aeromonas hydrophila infection. This research was using experimental method and the data were analyzed by descriptively. This study was using five treatments, Kn(were not immersed and infected), Kp (were not immersed Lawsonia inermis L. solution but infected of Aeromonas hydrophila), P1(dose Lawsonia inermis L. solution 2000 ppm), P2(3000 ppm), and P3(4000 ppm). The result shown that abnormalities liver tissues of Pangasius hypophthalmussuch us hemorrhage, hypertrophy and necrosis and kidney abnormalities such us hemorrhage, necrosis, and congestion. The best result was P1 of Pangasius hypophthalmus were immersed lawsonia inermis L. solution in preventing the Aeromonas hydrophila infection. Keyword:Histophatology, Liver, Kidney, Lawsonia inermis L.,Pangasius hypopthalmus